Educação e cidadania: aspectos legais, concepções e processos pedagógicos desenvolvidos na ETEC de Piedade-SP à luz de Gramsci - Domingues, Tiago César (Universidade Federal de São Carlos, 2017)
This dissertation resultes of a bibliographical, documentary and field research on the senses, the conceptions and the pedagogical processes related to citizenship, developed at ETEC de Piedade in São Paulo. Firstly, it was made a historical survey in which the meanings of the concept citizenship present from antiquity to the present day were identified. The liberal conception of citizenship in Marshall, formulated from the observation to the British society in the middle of the century XX, lists as central the categories of civil, political and social rights as status. Pizzorno presents the "System of Solidarity" and the "System of Interest" as regents of political action. In Severino, the conception of citizenship based on the categories of material, symbolic and political goods stands out, which the subject needs to enjoy to be considered a citizen. Saviani offers reading keys to understand Gramsci's theoretical-methodological legacy, which is the main reference of the research. Based on this reference, the meanings of the concept of "citizenship" present in the legal norms that guide the organization of educational systems and the educational processes of secondary and technical-vocational education, such as: LDB 9394/96, the Guidelines National Curriculares for High School and Technical-Vocational, as well as the Political Project Pedagogical of the researched school unit. Questionnaires were applied, with open and closed questions to 10 teachers and 30 students of the Etec de Piedade school, in order to capture datum about the conception and practice of teachers regarding citizenship. Finally, as a result of this research, the polissemias, the generalities and the limitations of the educational systems in the organization of elements imbricated in the educational processes of social quality, as well as the documentary conceptual incoherencies, in the conceptions and practices related to the education for the Citizenship in the Marxist-Gramscian sense
Education and citizenship: legal aspects, conceptions and pedagogical processes developed in the ETEC of Piedade-SP in the light of Gramsci
Keywords: cidadania; Gramsci; LDBN 9394/96; Diretrizes Curriculares Nacionais; ensino profissionalizante; CIENCIAS HUMANAS::EDUCACAO